Implementation of the Quality of The Health Center Management Information System and Work Culture in Improving Employee Performance at The Simolawang Surabaya Health Center - Tri Sulistyaning Ati (International Journal of Social, Economic, and Business, 2025)
This study is motivated by the non-optimal utilization of the Puskesmas Management Information System (SIMPUS) and work culture at Puskesmas Simolawang Surabaya which has an impact on employee performance. Several problems such as manual reports that are still carried out, network disruptions, low employee understanding of SIMPUS, and uneven application of the 3S work culture (Smile, Salam, Sapa) indicate the need for in-depth evaluation. This study aims to analyze the implementation of SIMPUS system quality and work culture in improving employee performance at Puskesmas Simolawang. The method used is descriptive quantitative approach with data collection techniques through questionnaires and observation of 45 respondents using total sampling technique. The results showed that SIMPUS system quality was in the good category, employee work culture was quite good, and employee performance was also in the good category. Based on validity and reliability tests, most questionnaire items were declared valid and reliable. The findings show that system quality and work culture contribute positively to improving employee performance. In conclusion, strengthening the implementation of information systems and internalizing a more effective work culture are needed to support optimal health services.